ENFAATAN UANG SIMPAN PINJAM PADA BADAN USAHA MILIK DESA (BUMDES) DI DESA LUBUK TILAN KECAMATAN DAYUN KABUPATEN SIAK SRI INDRAPURA - Susanti Br Siregar; T. Romi Marnelly (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This study entitled "Utilization of Savings and Loans in Village-Owned Enterprises (BUMDES) of Lubuk Tilan Village, Dayun District, Siak Sri Indra Pura District" data that can be done to answer the debate made by this researcher is quantitative research, which was approved by the Loan Funds lent from BUMDES Unit Mawar Abadi Savings and Loans which will then be analyzed with the theories in this study. The following is the formulation of the problem (1) How is Mawar Abadi's BUMDes Savings and Loans for BUMDes Mawar Abadi user communities in Lubuk Tilan Village, Dayun District, Siak Sri Indrapura Regency? (2) Lubuk Tilan, Dayun Subdistrict, Siak Sri Indrapura Regency? In this data collection technique is a questionnaire, as well as documentation, as for a number of populations and samples using Slovin techniques from 450 populations in 78 populations and findings in the field that we can find out about BUMDes Savings and Loans grants for venture capital and business types what is successful in a Savings and Loan Business Fund is a successful business, which is an oil palm business, while an unsuccessful business is a trading business.Keywords : Utilization, saving  and Loans. BUMDES, Mawar Abadi